Transatlantic Caribbean: Dialogues of People, Practices, Ideas - Kummels, Ingrid; Rauhut, Claudia; Rinke, Stefan; Timm, Birte (Global Studies, 2014)
»Transatlantic Caribbean« widens the scope of research on the Caribbean by focusing on its transatlantic interrelations with North America, Latin America, Europe and Africa and by investigating long-term exchanges of people, practices and ideas. Based on innovative approaches and rich empirical research from anthropology, history and literary studies the contributions discuss border crossings, south-south relations and diasporas in the areas of popular culture, religion, historical memory as well as national and transnational social and political movements. These perspectives enrich the theoretical debates on transatlantic dialogues and the Black Atlantic and emphasize the Caribbean's central place in the world.